A New Type-2 Soft Set: Type-2 Soft Graphs and Their Applications. (18th October 2017) - Hayat, Khizar; Ali, Muhammad Irfan; Cao, Bing-Yuan; Yang, Xiao-Peng
Abstract : The correspondence between a vertex and its neighbors has an essential role in the structure of a graph. Type-2 soft sets are also based on the correspondence of primary parameters and underlying parameters. In this study, we present an application of type-2 soft sets in graph theory. We introduce vertex-neighbors based type-2 soft sets overX (set of all vertices of a graph) andE (set of all edges of a graph). Moreover, we introduce some type-2 soft operations in graphs by presenting several examples to demonstrate these new concepts. Finally, we describe an application of type-2 soft graphs in communication networks and present procedure as an algorithm.